A Comparative Study of Articular Chondrocytes Metabolism on a Biodegradable Polyesterurethane Scaffold and Alginate Beads in Different Oxygen Tension and pH - Saeed Karbasi (مجله دانشکده پزشکی اصفهان, 2009)
Background: Cartilage is a tissue with a low potency of self-repairing. One of the methods in increasing of regeneration and metabolism in cartilge, is stimulating physicochemical parameters on cell-polymer systems, as cartilage based cells. The cell–polymer system can be used to identify and control various biochemical and physical factors expected to influence cell function and tissue growth. Methods: Two physicochemical parameters, oxygen tension and pH, was changed to measure the lactate and rate of lactate production after 1, 2 and 3 days culture and GAG (glycosaminoglycan) production after 3, 7 and 14 days culture of chondrocytes on DegraPol®, as a biodegradable polyurethane scaffold (BPUS), and alginate scaffolds. The results finally were compared on both scaffolds. Findings: Physicochemical parameters like oxygen tension and pH could change cell metabolism. In fact, the physicochemical parameters could affect lactate production and GAG content of chondrocyte cells and it does not depend on the type of scaffold. The best condition of the articular chondrocytes metabolism was for 5% O2 and pH = 7.4 (P < 0.001). The comparison between BPUS and alginate scaffold is showing that the results are better for alginate beads (P < 0.001). Conclusion: Oxygen and pH alterations could change the cell volume that cause changing of normal mechanism of transferring ions and other digesting solutes into the cells. Therefore, optimization of oxygen tension and pH could optimize glycolysis process in cartilage. Also, hydrophilicity of alginate causes better cell distribution and nutrition than BPUS.